Late Follow-up of Patients Submitted to Total Cavopulmonary Derivation: Clinical Aspects, Reinterventions, and Complications Interfering in Morbidity and Mortality - Pessotti,Cristiane Felix Ximenes (2018)
Abstract Objective: To identify main complications in outpatient follow-up, as well as factors before or during operation that may interfere in patient's evolution. Methods: Retrospective study of patients submitted to total cavopulmonary shunt with extracardiac conduit from 2000 to 2014 at the Hospital do Coração (São Paulo, Brazil) and who underwent clinical follow-up at this institution. Results: One hundred and fifty surgeries were performed and 59 patients maintained outpatient follow-up. The mean age of these patients at the time of surgery was 4.45 years (median of 45 months) and 70.2% of them were males. Among the patients undergoing outpatient follow-up, postoperative time at evaluation ranged from 10 days to 145 months; 30 (50.8%) patients had single left ventricle and 29 (49.2%) had single right ventricle (48.2% of these presented with hypoplastic left heart syndrome [HLHS]). Patients with single left ventricle had a higher percentage of reintervention-free survival, but without statistically significant difference. 40% of the patients had no complications and 35% of them presented with thrombosis at some point in the follow-up period, with ventricular dysfunction being the second most frequently found complication (15% of cases), mainly among patients with single right ventricle morphology (P=0.04). Between the patients currently under follow-up, 20 (35%) of them had been evaluated by ultrasonography and had some degree of hepatic congestion and/or hepatomegaly. 16.7% of the patients with such alteration had HLHS (P=0.057). Conclusion: Except for the right ventricular morphology, no other factor has been shown to interfere in late evolution after total cavopulmonary shunt.